BIROKRASI PEMERINTAHAN: PENYEDERHANAAN DAN TANTANGANNYA DALAM MENCIPTAKAN GOOD GOVERNANCE - Fanila kasmita Kusuma (LPSDI Bina Patria, 2024)
The rapid development of technology requires the government to innovate and reform the bureaucracy to create good governance. One that can be used is to implement e-governance. The purpose of this study is to find out how the simplification and challenges faced by the government bureaucracy in creating good governance in this technological era. This research method is using a qualitative method with a literature study as a data collection technique. The results of this study indicate that in improving the good governance of today's government, it can be done by increasing electronic-based government services or what is commonly referred to as E-Government. The challenges faced by the government include: 1) Culture is a challenge that inevitably becomes the first obstacle in the digital transformation process. 2) In carrying out collaboration, there are often differences in authority, permits, and so on. 3) The development of digital technology requires employees or ASN to adapt and understand technology